Modern diplomacy - Barston, R. P. (Ronald Peter) (London ; New York : Routledge, Taylor & Francis Group, 2019)
"Contemporary, thoughtful and extensively illustrated, Modern Diplomacy examines a broad range of current diplomatic practice. This leading and widely used book - now in its fifth edition - equips students with a detailed analysis of important international issues that reflect and impact upon diplomacy and its relations. The subject is bought to life through case studies and examples which highlight the working of contemporary diplomacy within the international political arena. Organised around five broad topic areas, including the nature of diplomacy, diplomatic methods negotiation, the operation of diplomacy in specific areas and international conflict, the book covers all major topic areas of contemporary diplomacy. New features for this edition: - Developments in diplomatic practice; - Strategies in diplomacy; - International trade, geopolitics and agreements; - Diplomacy of new regional organisations and groupings; - Developing country diplomacy; - Non-traditional diplomacy; - New concepts - parallel and counter diplomacy; - New case studies include: the Paris Climate Agreement, Brexit, international finance and trade agreements, and the UN security forces. Modern Diplomacy is essential reading for students and practitioners of international relations, foreign policy, international law, international political economy, international economics, the Foreign Services Institutes and the National Diplomatic Academies"--
The changing nature of diplomacy -- Foreign policy organisation -- Diplomatic methods -- Negotiation -- Developing diplomatic practice -- Groups and networks -- Regional organisations and diplomacy -- Cyber diplomacy -- International financial relations -- Trade, foreign policy and diplomacy -- Environmental diplomacy -- Environmental diplomacy: case examples -- Disaster and emergency diplomacy -- Diplomacy and security -- Diplomacy and mediation -- The diplomacy of normalisation -- Diplomatic correspondence: case examples -- International treaties -- International agreements: case examples -- Paris Agreement.
Includes bibliographical references and index.
Keywords: Diplomacy